Գիտության ոլորտում հայ-ֆրանսիական համագործակցությունը 1992-2013 թթ. - Բաղդասարյան, Տիգրան (YSU Journal of International Affairs, 2014)
This paper analyzes the legal basis, main directions andexisting obstacles, as well as possible perspectives of bilateral cooperation between theRepublic of Armenia and the French Republic in the sphere of science. Being a weaklink in the Armenian-French cultural, educational and scientific relations, scientificcooperation between Armenia and France has developed rather slowly. However, since2008 the cooperation in this sphere has fixed a positive shift, which was determined bynew agreements and increased attention to the issue by Armenia and France.
Keywords: Armenia, France, Armenian-French relations, science, education, scientific cooperation, archaeological exploration